Horizontal Cleavage Meniscus Tear Treated With All-inside Circumferential Compression Stitches - Jarret M. Woodmass, M.D., F.R.C.S.C.; Joshua D. Johnson, M.D.; Isabella T. Wu, B.A.; Daniel B.F. Saris, M.D., Ph.D.; Michael J. Stuart, M.D.; Aaron J. Krych, M.D. (Arthroscopy Techniques, 2017)
Horizontal cleavage meniscus tears are a common orthopedic injury often treated with partial or total meniscectomy versus repair. This Technical Note presents a technique for all-inside repair with uniform compression of the superior and inferior leaflets by placement of multiple circumferential compression stitches using an all-inside self-retrieving suture passing device. The currently described technique provides several advantages for all-inside repair of a horizontal cleavage tear: (1) eliminates the need for a posterior incision, (2) minimizes the risk of neurovascular injury, (3) uses standard arthroscopy portals (or small modifications), and (4) requires only a single suture deployment with a self-retrieving device for each circumferential compression stitch. The resulting circumferential stitch provides uniform compression to the superior and inferior leaflets, promoting meniscal healing. This configuration has been shown to have the highest load to failure of all repair patterns.